Factores determinantes de la demanda de crédito bancario privado en moneda nacional en el Perú, período 2000:T1-2015:T4 - Guevara Recoba, Victor Saúl Isidro (2017)
This research aims to determine the factors that affect the demand for private bank credit in Peruvian currency: period 2000: T1-2015: T4. For which the nonexperimental research approach was used. Longitudinal cut. The research presents an explanatory scope since it is made known because the variables influence in a positive or negative way, for which the information collected in the theoretical framework was used. The results show an alignment with the predictions of economic theory. To reach these, the SPSS statistical program was analyzed by analyzing the data using the Pearson correlation coefficient. It was found that the determinant factors of the demand of private bank credit in national currency are real GDP (positive incidence), TIAME (positive incidence) and CPI (positive incidence).